Human toxoplasmosis: a systematic review for genetic diversity of Toxoplasma gondii in clinical samples. (5th November 2019) - Hosseini, S. A.; Amouei, A.; Sharif, M.; Sarvi, Sh.; Galal, L.; Javidnia, J.; Pagheh, A. S.; Gholami, S.; Mizani, A.; Daryani, A.
Abstract: Toxoplasma gondii ( T. gondii ) as an obligate intracellular protozoan with a worldwide distribution can infect virtually all warm-blooded animals and humans. This study aims to provide a summary of the available data on genotypes of T. gondii in human. Five databases including MEDLINE in PubMed, Scopus, Science Direct, Web of Science and Google Scholar were searched for the T. gondii genotyping in human during 1995–August 2017. Next, we screened all the articles based on the inclusion and exclusion criteria. Overall, 26 studies were eligible regarding genotyping T. gondii in human samples. In clonal genotyping, 167 out of 286 cases (58%) were infected with type II. Genetic characterisation of T. gondii isolates displayed that type II was the most predominant genotype in human with the prevalence of 64.3%, 62.1% and 41.7% in patients with AIDS, congenital and ocular toxoplasmosis, respectively. In ToxoDB genotyping, most individuals were infected with genotypes #9 and #65 (21.2%). Based on these results, genotype profile of T. gondii isolates is different throughout the world. The strains in Asian and African countries are characterised by low genetic diversity, while in North and South America a wide diversity of this parasite is found. In countries without any data (e.g. Australia, Western and Southern Africa and Western Asia), identification of T. gondii genotypes might discover higher genetic diversity.